Four major task domains of science for sustainability - Arlette Jappe-Heinze (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2006)
We propose a research agenda integrating environment-related science, technology, and innovation (STI) using a problem-solving approach to sustainable development. We argue that STI for sustainability encompasses four major task domains: (1) ecological modernization and transformation, (2) ecosystem management, (3) environmental risk assessment, and (4) adaptation to environmental change, each posing great social challenges. For each domain, nature-society interaction increasingly relies on knowledge acquisition. The proposed agenda focuses on the investigation of R&D capacity and linking knowledge and action within and among societal spheres (i.e., science, politics, business, law, mass media, and education). While today the disciplinary niches of environment-related STI research are still fragmented, with this broader framework, STI research could develop into a major social science field of human-environment relations.
urn:nbn:de:0011-n-494715
Keywords: 330; human dimensions of global environmental change; environmental sociology; science for sustainability; STI research; innovation research; social studies of science; so-ciology of knowledge; nature-society interaction; noosphere; ecological modernization; ecosystem management; environmental risk assessment; adaptation to environmental change; Forschungs- und Technologiepolitik; Umweltforschung; Sozialforschung; Nachhaltige Entwicklung